Qualitative and quantitative analyses of unemployment in Malaysia - De Vries, Anton Eise (2015)
This paper attempts to provide a overview of the determinants of unemployment in Malaysia. Unemployment’s influencing factors are traditionally described as either micro- or macroeconomic to a nation. A qualitative investigation of the microeconomic variables for unemployment in Malaysia and a quantitative time series analysis of macroeconomic variables for unemployment in Malaysia are made. The shift of the secondary sector towards thetertiary sector and the use of high-tech production is held to be of importance for the unemploymentrate in Malaysia. On a macroeconomic level, GDP per capita and the inflation rate, Okun’s Law and the Phillips Curve, are analyzed. This study provides an overview of Malaysian unemployment in both a qualitative and quantitative sense. It forms the foundation of comparison of economical phases gone through by developed countries.